2002
DOI: 10.1256/00359000260498806
|View full text |Cite
|
Sign up to set email alerts
|

A classification of FASTEX cyclones using a height‐attributable quasi‐geostrophic vertical‐motion diagnostic

Abstract: SUMMARYA systematic and objective procedure is developed for applying the simple cyclone classi cation scheme of Petterssen and Smebye. This method uses a height-attributable solution of the quasi-geostrophic ! equation to identify and quantify the relative importance of upper-and lower-tropospheric forcing and also the time trend in the horizontal spacing of the forcing at these two levels. By applying this classi cation method to a sample of cyclogenesis events, during their maximum intensi cation stage, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
112
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 37 publications
(26 reference statements)
2
112
0
Order By: Relevance
“…Other studies, for example, Pinto et al (2007Pinto et al ( , 2009, have shown an increase in the upper air baroclinicity, as well as an increase in the polar jet intensity, specifically for the North Pacific basin. Dacre and Gray (2009) also suggest an increase in high-latitude cyclones that are formed when a large upper level trough moves over the ocean (Deveson et al, 2002), due to a warmer climate. A better understanding of the diabatic processes that occur in storms is needed to better inform whether the increase in precipitation will lead to such consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, for example, Pinto et al (2007Pinto et al ( , 2009, have shown an increase in the upper air baroclinicity, as well as an increase in the polar jet intensity, specifically for the North Pacific basin. Dacre and Gray (2009) also suggest an increase in high-latitude cyclones that are formed when a large upper level trough moves over the ocean (Deveson et al, 2002), due to a warmer climate. A better understanding of the diabatic processes that occur in storms is needed to better inform whether the increase in precipitation will lead to such consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 4c) was also identified by Gray and Dacre (2006) as main source region of cyclones of type B following the threefold classification scheme of extratropical cyclogenesis by Deveson et al (2002), an extension of the classification by Petterssen and Smebye (1971). This type B of cyclone development is predominantly upper-level forced.…”
mentioning
confidence: 85%
“…Finally, Plant et al [2003] showed that midlevel PV anomalies, generated in response to latent heating, were important for the development of two socalled type C cyclones. Type C cyclones are characterised by strong (quasigeostrophic) upper-level forcing, very weak low-level forcing and a vertical upstream tilt that remains constant or increases as the cyclone intensifies [Deveson et al, 2002]. Dacre and Gray [2009] found, in a 6-year climatology of North Atlantic cyclones, that a larger proportion of east than west Atlantic cyclones showed characteristics of type C development (39% compared to 25%), consistent with the generally weaker low-level frontal gradients in the east North Atlantic.…”
Section: Introductionmentioning
confidence: 99%